Full-regenerated geopolymer concrete as well as preparation method and application thereof

By using solid waste such as recycled powder, fly ash, slag, and bagasse ash as alkali activaters in concrete, fully recycled polymer concrete was developed, solving the problems of carbon emissions and resource consumption of traditional cement-based concrete, and achieving low-carbon and environmentally friendly construction results.

CN119874267APending Publication Date: 2025-04-25广西平陆运河建设有限公司 +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510022989.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing cement-based concrete will release a large amount of carbon dioxide during the production process, resulting in carbon emissions and environmental pollution. In addition, traditional mold bag concrete consumes a lot of natural resources, making it difficult to achieve low-carbon and environmentally friendly construction goals.

Method used

Fully recycled land polymer concrete is used to form a low-carbon, environmentally friendly gelling material by using solid waste such as recycled powder, fly ash, slag, etc. as the ground polymer precursor, and using bagasse ash to replace sodium silicate as the source of silicon elements in the alkali exciter.

Benefits of technology

It has achieved the characteristics of low hydration heat, high mobility and rapid development in early intensity, reduced resource consumption and carbon emissions, and is suitable for canal waterways, slope protection and bank protection projects, meeting the low-carbon and environmentally friendly construction needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874267A_ABST
    Figure CN119874267A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of geopolymer concrete. The invention provides fully-recycled geopolymer concrete and a preparation method and application thereof.The fully-recycled geopolymer concrete comprises recycled coarse aggregate, recycled fine aggregate, a water reducing agent, water, a geopolymer precursor and a composite alkali activator, the geopolymer precursor comprises at least one of recycled micro powder, fly ash and slag, and the preparation method of the fully-recycled geopolymer concrete is further provided. The coarse aggregate, the fine aggregate and the geopolymer precursor of the fully-recycled geopolymer concrete are all composed of solid waste, the fully-recycled geopolymer concrete is green and low-carbon, the concrete expansion degree is 500 mm or above, the fully-recycled geopolymer concrete has the characteristics of low hydration heat, high fluidity and rapid early strength development, and meanwhile, the fully-recycled geopolymer concrete can meet the application requirements of good fluidity, rapid curing and early use of mold bag concrete, and has wide application prospects. The method can be applied to projects such as canal channels, slope protection and bank protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of geopolymer concrete, and in particular relates to a fully recycled geopolymer concrete and a preparation method and application thereof. Background Art

[0002] In traditional construction, cement-based concrete is mostly used. Cement is one of the main sources of carbon emissions in the construction industry. Its production process releases a large amount of carbon dioxide, exacerbating environmental degradation. With the global emphasis on environmental protection and sustainable development, the protection of natural resources and the recycling of waste have gradually become important issues in social development. Against this background, the sustainable and low-carbon development of concrete materials has become an inevitable trend in the industry.

[0003] In order to reduce the carbon emissions of concrete and the consumption of natural resources, attempts have been made to add solid waste as an alternative material to concrete. For example, patent CN 115321933 A discloses a binder containing a new anti-caking agent, a mold bag concrete, and its preparation and application, wherein industrial by-product gypsum and incineration ash and other solid wastes are used as components of the binder, reducing the amount of cement. Patent CN 101456705 A discloses a hydraulic mold bag concrete using industrial solid waste, wherein the coarse aggregate uses steel slag or tailings, the fine aggregate uses tailings sand or fly ash coarse sand or river sand, and the binder uses steel slag, fly ash, silicate cement clinker, slag, and industrial waste gypsum, saving the consumption of natural resources. These explorations have reduced the environmental impact of concrete to a certain extent, but since the cementitious materials of the above concrete still rely on cement, it is difficult to further reduce carbon emissions.

[0004] In addition, the consumption of natural resources by traditional bagged concrete is also an issue that cannot be ignored. Existing bagged concrete is a concrete construction technology that uses a flexible bag as a template, injects concrete into the bag through a concrete pump, and solidifies the concrete into a predetermined shape or structure under the constraint of the bag to meet specific usage requirements. Bagged concrete is commonly used in water conservancy projects, coastal protection, flood control dams, etc., and has waterproofing, anti-seepage, ecological slope protection and other projects. It has the characteristics of flexible construction, short cycle, strong adaptability, and can adapt to complex terrain and underwater operations; good structural integrity, good durability, and low maintenance cost; at the same time, it can also reduce environmental damage and promote ecological restoration. It is an economical and environmentally friendly engineering material.

[0005] In view of this, it has become particularly urgent to develop a new type of concrete that is low-carbon, environmentally friendly, and resource-saving. Realizing the green transformation of concrete materials through technological innovation will help promote the sustainable development of the construction industry and help achieve the "dual carbon" goal. Summary of the invention

[0006] In order to solve the problems of the prior art, the present invention provides a fully recycled geopolymer concrete and a preparation method and application thereof. The fully recycled geopolymer concrete not only has the characteristics of low hydration heat, high fluidity and rapid early strength development, but also is low-carbon, environmentally friendly and economical, and can be applied to canal waterways, slope protection and revetment projects.

[0007] The object of the present invention is to provide a fully recycled geopolymer concrete, comprising the following components in parts by weight:

[0008]

[0009] Wherein, the above-mentioned geopolymer precursor includes at least one of recycled micro powder, fly ash and slag components.

[0010] The fully recycled geopolymer concrete aggregate of the present invention is recycled coarse and fine aggregates, the geopolymer mixed precursor is composed of at least one of recycled micropowder, fly ash and slag, and the geopolymer cementitious material composed of solid waste geopolymer precursor and composite alkali activator replaces cement. The components are all solid waste. By utilizing these wastes, the present invention not only greatly reduces resource consumption and realizes local material utilization, but also effectively reduces transportation costs, reflecting the dual benefits of environmental protection and economy.

[0011] Preferably, the preparation method of the composite base activator comprises the following steps:

[0012] (1) After calcining bagasse at 600-800° C. for 1-2 hours, the bagasse is ground in a ball mill for 10-40 minutes to obtain bagasse ash;

[0013] (2) The bagasse ash and 7-9M NaOH solution are mixed in a mass ratio of 1:4, stirred for 5-15 minutes to obtain a mixed solution, sealed and stored, and allowed to stand for 12-36 hours to allow the bagasse ash to fully dissolve, thereby obtaining a composite alkali activator.

[0014] The present invention uses solid waste bagasse ash to replace expensive sodium silicate as the source of silicon in the alkali activator, thereby reducing costs. The bagasse ash is soaked in NaOH solution to release soluble silicon dioxide, promote the formation of aluminosilicate polymer chains, and improve the performance of geopolymers.

[0015] Preferably, the geopolymer precursor comprises, by weight, 30-50 parts of recycled micropowder, 0-40 parts of fly ash, and 30-70 parts of slag.

[0016] In the present invention, the recycled coarse aggregate is obtained from the demolished concrete of abandoned buildings, abandoned dams or abandoned rivers after crushing, particle shaping and screening. The particle grading is a continuous aggregate of 5-16 mm, and the coarse aggregate grade is Class II and above.

[0017] Recycled fine aggregate is obtained from mortar blocks from abandoned buildings, abandoned dams or abandoned rivers after crushing, particle shaping and screening. Its particle grading is a continuous aggregate of 0.15-4.75mm, and the fine aggregate grade is Class II and above.

[0018] Regenerated micro powder is obtained by grinding, magnetic separation and secondary grinding of waste sintered clay bricks, and its technical indicators are level II and above.

[0019] In the present invention, the water reducer is at least one of a naphthalene-based water reducer, a polycarboxylic acid water reducer and a sodium lignin sulfonate water reducer.

[0020] The present invention also aims to provide a method for preparing the above-mentioned fully recycled geopolymer concrete, comprising the following steps:

[0021] (1) Weighing each component according to the above ratio, mixing the above geopolymer precursor and recycled fine aggregate evenly, and then adding recycled coarse aggregate and mixing evenly to obtain a mixture;

[0022] (2) mixing the water reducer with part of the water to obtain a water reducer solution;

[0023] (3) Add the composite alkali activator and the remaining amount of water to the mixture obtained in step (1), mix them evenly, then add the water reducer solution obtained in step (2), mix them evenly, and obtain fully recycled geopolymer concrete.

[0024] The present invention also aims to provide a fully recycled geopolymer concrete in a mold bag, and a preparation method thereof, comprising the steps of pressing the fully recycled geopolymer concrete into a mold bag at a pouring rate of 5-20 m / s. 3 / h, and curing for 3-14 days to obtain fully recycled mold bag geopolymer concrete.

[0025] The purpose of the present invention is also to provide an application of the above-mentioned fully recycled mold bag geopolymer concrete, and to apply the above-mentioned fully recycled mold bag geopolymer concrete to projects such as canal waterways, slope protection and bank protection.

[0026] Among the alkali-activated materials, a mixture of sodium silicate and NaOH is the most commonly used alkali activator. Among them, sodium silicate, as a key raw material, is not only expensive, but also has huge carbon emissions. The present invention achieves the dual goals of reducing costs and reducing carbon emissions by using sugar factory solid waste - bagasse ash, to replace sodium silicate as the source of silicon in the alkali activator. Specifically, the bagasse ash is soaked in NaOH solution to release the soluble silica therein, promote the formation of aluminosilicate polymer chains, and improve the performance of geopolymers. This method not only realizes the resource utilization of bagasse ash, but also reduces carbon emissions, showing great environmental protection potential.

[0027] The coarse and fine aggregates used in the present invention are recycled coarse and fine aggregates obtained by processing concrete from abandoned buildings, abandoned dams or abandoned river channels; the geopolymer mixed precursor is composed of two or three of recycled micro powder, fly ash and slag, and the components are all solid wastes. By utilizing these wastes, the present invention not only greatly reduces resource consumption and realizes local materials, but also effectively reduces transportation costs, reflecting the dual benefits of environmental protection and economy.

[0028] Compared with the prior art, the fully recycled geopolymer concrete of the present invention has the following beneficial effects:

[0029] (1) Coarse aggregate, fine aggregate and geopolymer precursor are all made of solid waste, which is green and low-carbon;

[0030] (2) The composite alkaline activator uses solid waste bagasse ash to replace the more expensive sodium silicate as the source of silicon in the alkaline activator, which reduces the cost. The bagasse ash is soaked in NaOH solution to release the soluble silica, promote the formation of aluminosilicate polymer chains, and improve the performance of geopolymers.

[0031] (3) Compared with cement-based materials, the heat of hydration is lower;

[0032] (4) The concrete expansion is above 500 mm and has high fluidity;

[0033] (5) The initial setting time shall not be earlier than 45 minutes;

[0034] (6) Early strength development is fast, and the compressive strength can reach 3-5MPa or above in 3 days.

[0035] In summary, the fully recycled geopolymer concrete of the present invention, through the synergistic effect of various industrial solid wastes, has the characteristics of low hydration heat, high fluidity, moderate setting time and rapid early strength development. In addition, these characteristics can also meet the application requirements of good fluidity, rapid solidification and early use of mold bag concrete, and can be applied to canal waterways, slope protection and bank protection projects. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a flow chart of the preparation method of fully recycled mold bag geopolymer concrete in Example 1. DETAILED DESCRIPTION

[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The recycled coarse aggregate in the embodiment of the present invention is obtained by crushing, particle shaping and screening the demolished concrete of abandoned buildings, abandoned dams or abandoned rivers. The particle grading is a continuous aggregate of 5-16 mm, and the coarse aggregate grade is Class II and above.

[0039] Recycled fine aggregate is obtained from mortar blocks from abandoned buildings, abandoned dams or abandoned rivers after crushing, particle shaping and screening. Its particle grading is a continuous aggregate of 0.15-4.75mm, and the fine aggregate grade is Class II and above.

[0040] Regenerated micro powder is obtained by grinding, magnetic separation and secondary grinding of waste sintered clay bricks, and its technical indicators are level II and above.

[0041] Example 1

[0042] 1. Preparation of composite alkali activator

[0043] Step A1: sugarcane bagasse, a solid waste from a sugar refinery, is calcined at 800° C. for 2 h and then ground in a ball mill for 40 min to obtain bagasse ash;

[0044] Step A2: Mix bagasse ash and 8M NaOH solution in a mass ratio of 1:4, and stir for 15 minutes to obtain a mixed solution;

[0045] Step A3: The mixed solution is sealed and stored, and allowed to stand for 24 hours to allow the bagasse ash to fully dissolve, thereby obtaining a composite alkali activator.

[0046] 2. Preparation of fully recycled geopolymer concrete

[0047] Step B1: Weigh the following components by mass: 280 parts of recycled coarse aggregate, 140 parts of recycled fine aggregate, 8 parts of composite alkali activator, 0.3 parts of polycarboxylic acid high-performance water reducer, 50 parts of water, and a geopolymer precursor made by mixing 50 parts of recycled micropowder and 50 parts of slag.

[0048] Step B2: The geopolymer precursor and the recycled fine aggregate are placed in a mixer and mixed for 1 minute, and then the recycled coarse aggregate is added and stirred for 1 minute to obtain a mixture.

[0049] Step B3: Take an appropriate amount of water to dissolve the high-performance water-reducing agent to obtain a high-performance water-reducing agent solution; then, add the composite alkali activator and the remaining water into the mixer, stir for 3 minutes, then add the high-performance water-reducing agent solution, stir for 3 minutes, and obtain a freshly mixed fully recycled geopolymer concrete.

[0050] 3. Preparation of fully recycled geopolymer bag concrete

[0051] Use a concrete pump to press the freshly mixed fully recycled geopolymer concrete into the mold bag, and control the pouring rate at 15m 3 / h, after being filled, use cable ties to tie it up, cover it with grass and sprinkle water for 3 days to obtain fully recycled mold bag geopolymer concrete.

[0052] Example 2

[0053] 1. The preparation of the composite base activator is the same as that in Example 1.

[0054] 2. Weigh the following components by mass: 280 parts of recycled coarse aggregate, 140 parts of recycled fine aggregate, 8 parts of composite alkali activator, 0.4 parts of polycarboxylic acid high-performance water reducer, 40 parts of water, and the geopolymer precursor is a mixture of 40 parts of recycled micropowder and 60 parts of slag.

[0055] The preparation method of fully recycled geopolymer concrete is the same as that in Example 1.

[0056] 3. In the preparation of fully recycled mold bag geopolymer concrete, the pouring rate is 20m 3 / h, and the remaining steps are the same as in Example 1.

[0057] Example 3

[0058] 1. The preparation of the composite base activator is the same as that in Example 1.

[0059] 2. Weigh the following components by mass: 280 parts of recycled coarse aggregate, 140 parts of recycled fine aggregate, 8 parts of composite alkali activator, 0.2 parts of polycarboxylic acid high-performance water reducer, 45 parts of water, and the geopolymer precursor is a mixture of 30 parts of recycled micropowder and 70 parts of slag.

[0060] The preparation method of fully recycled geopolymer concrete is the same as that in Example 1.

[0061] 3. In the preparation of fully recycled mold bag geopolymer concrete, the pouring rate is 10m 3 / h, and the remaining steps are the same as in Example 1.

[0062] Example 4

[0063] 1. The preparation of the composite base activator is the same as that in Example 1.

[0064] 2. Preparation of fully recycled geopolymer concrete

[0065] Step B1: Weigh the following components by mass: 280 parts of recycled coarse aggregate, 140 parts of recycled fine aggregate, 8 parts of composite alkali activator, 0.1 parts of polycarboxylic acid high-performance water reducer, 30 parts of water, and a geopolymer precursor prepared by mixing 30 parts of recycled micro powder, 30 parts of fly ash, and 40 parts of slag;

[0066] Step B2: placing the geopolymer precursor and the recycled fine aggregate in a mixer and mixing them for 2 minutes, then adding the recycled coarse aggregate and stirring for 3 minutes to obtain a mixture;

[0067] Step B3: Take an appropriate amount of water to dissolve the high-performance water-reducing agent to obtain a high-performance water-reducing agent solution; then, add the composite alkali activator and the remaining water into the mixer, stir for 3 minutes, then add the high-performance water-reducing agent solution, stir for 3 minutes, and obtain a freshly mixed fully recycled geopolymer concrete.

[0068] 3. Preparation of fully recycled mold bag geopolymer concrete

[0069] Use a concrete pump to press the freshly mixed fully recycled geopolymer concrete into the mold bag, and control the pouring rate at 15m 3 / h, after being filled, use cable ties to tie it up, cover it with grass and sprinkle water for 3 days to obtain fully recycled mold bag geopolymer concrete.

[0070] Example 5

[0071] 1. The preparation of the composite base activator is the same as that in Example 1.

[0072] 2. Preparation of fully recycled geopolymer concrete

[0073] Step B1: Weigh the following components by mass: 280 parts of recycled coarse aggregate, 140 parts of recycled fine aggregate, 10 parts of composite alkali activator, 0.1 parts of naphthalene-based high-performance water reducer, 30 parts of water, and a geopolymer precursor prepared by mixing 30 parts of recycled micro powder, 30 parts of fly ash, and 40 parts of slag;

[0074] Step B2: placing the geopolymer precursor and the recycled fine aggregate in a mixer and mixing them for 2 minutes, then adding the recycled coarse aggregate and stirring for 3 minutes to obtain a mixture;

[0075] Step B3: Take an appropriate amount of water to dissolve the high-performance water-reducing agent to obtain a high-performance water-reducing agent solution; then, add the composite alkali activator and the remaining water into the mixer, stir for 3 minutes, then add the high-performance water-reducing agent solution, stir for 3 minutes, and obtain a freshly mixed fully recycled geopolymer concrete.

[0076] 3. Preparation of fully recycled mold bag geopolymer concrete

[0077] Use a concrete pump to press the freshly mixed fully recycled geopolymer concrete into the mold bag, and control the pouring rate at 5m 3 / h, after being filled, use cable ties to tie it up, cover it with grass and sprinkle water for 3 days to obtain fully recycled mold bag geopolymer concrete.

[0078] Example 6

[0079] 1. The preparation of the composite base activator is the same as that in Example 1.

[0080] 2. Preparation of fully recycled geopolymer concrete

[0081] Step B1: Weigh the following components by mass: 280 parts of recycled coarse aggregate, 140 parts of recycled fine aggregate, 10 parts of composite alkali activator, 0.1 parts of sodium lignin sulfonate high-performance water reducer, and 40 parts of water. The geopolymer precursor is prepared by mixing 30 parts of recycled micro powder, 30 parts of fly ash, and 30 parts of slag;

[0082] Step B2: placing the geopolymer precursor and the recycled fine aggregate in a mixer and mixing them for 2 minutes, then adding the recycled coarse aggregate and stirring for 3 minutes to obtain a mixture;

[0083] Step B3: Take an appropriate amount of water to dissolve the high-performance water-reducing agent to obtain a high-performance water-reducing agent solution; then, add the composite alkali activator and the remaining water into the mixer, stir for 3 minutes, then add the high-performance water-reducing agent solution, stir for 3 minutes, and obtain a freshly mixed fully recycled geopolymer concrete.

[0084] 3. Preparation of fully recycled mold bag geopolymer concrete

[0085] Use a concrete pump to press the freshly mixed fully recycled geopolymer concrete into the mold bag, and control the pouring rate at 5m 3 / h, after being filled, use cable ties to tie it up, cover it with grass and sprinkle water for 3 days to obtain fully recycled mold bag geopolymer concrete.

[0086] Example 7

[0087] 1. Preparation of composite alkali activator

[0088] Step A1: sugarcane bagasse, a solid waste from a sugar factory, is calcined at 600° C. for 2 h and then ground in a ball mill for 10 min to obtain bagasse ash;

[0089] Step A2: Mix bagasse ash and 7M NaOH solution in a mass ratio of 1:4, and stir for 15 minutes to obtain a mixed solution;

[0090] Step A3: The mixed solution is sealed and stored, and allowed to stand for 12 hours to allow the bagasse ash to fully dissolve, thereby obtaining a composite alkali activator.

[0091] 2. Preparation of fully recycled geopolymer concrete

[0092] Step B1: Weigh the following components by mass: 300 parts of recycled coarse aggregate, 120 parts of recycled fine aggregate, 9 parts of composite alkali activator, 0.2 parts of polycarboxylic acid high-performance water reducer, and 35 parts of water. The geopolymer precursor is prepared by mixing 30 parts of recycled micro powder, 20 parts of fly ash, and 50 parts of slag;

[0093] Step B2: placing the geopolymer precursor and the recycled fine aggregate in a mixer and mixing them for 3 minutes, then adding the recycled coarse aggregate and stirring for 3 minutes to obtain a mixture;

[0094] Step B3: Take an appropriate amount of water to dissolve the high-performance water-reducing agent to obtain a high-performance water-reducing agent solution; then, add the composite alkali activator and the remaining water into the mixer, stir for 2.5 minutes, then add the high-performance water-reducing agent solution, stir for 3 minutes, and obtain a freshly mixed fully recycled geopolymer concrete.

[0095] 3. Preparation of fully recycled mold bag geopolymer concrete

[0096] Use a concrete pump to press the freshly mixed fully recycled geopolymer concrete into the mold bag, and control the pouring rate at 10m 3 / h, after being filled, use cable ties to tie it up, cover it with grass and sprinkle water for 3 days to obtain fully recycled mold bag geopolymer concrete.

[0097] Example 8

[0098] 1. Preparation of composite alkali activator

[0099] Step A1: sugarcane bagasse, a solid waste from a sugar refinery, is calcined at 700° C. for 1.5 h and then ground in a ball mill for 30 min to obtain bagasse ash;

[0100] Step A2: Mix bagasse ash and 9M NaOH solution in a mass ratio of 1:4, and stir for 5 minutes to obtain a mixed solution;

[0101] Step A3: The mixed solution is sealed and stored, and allowed to stand for 36 hours to allow the bagasse ash to fully dissolve, thereby obtaining a composite alkali activator.

[0102] 2. Preparation of fully recycled geopolymer concrete

[0103] Step B1: Weigh the following components by mass: 270 parts of recycled coarse aggregate, 150 parts of recycled fine aggregate, 9 parts of composite alkali activator, 0.2 parts of polycarboxylic acid high-performance water reducer, and 35 parts of water. The geopolymer precursor is prepared by mixing 30 parts of recycled micro powder, 20 parts of fly ash, and 50 parts of slag;

[0104] Step B2: placing the geopolymer precursor and the recycled fine aggregate in a mixer and mixing them for 2 minutes, then adding the recycled coarse aggregate and stirring for 2 minutes to obtain a mixture;

[0105] Step B3: Take an appropriate amount of water to dissolve the high-performance water-reducing agent to obtain a high-performance water-reducing agent solution; then, add the composite alkali activator and the remaining water into the mixer, stir for 2 minutes, then add the high-performance water-reducing agent solution, stir for 2.5 minutes, and obtain a freshly mixed fully recycled geopolymer concrete.

[0106] 3. Preparation of fully recycled mold bag geopolymer concrete

[0107] Use a concrete pump to press the freshly mixed fully recycled geopolymer concrete into the mold bag, and control the pouring rate at 10m 3 / h, after being filled, use cable ties to tie it up, cover it with grass and sprinkle water for 3 days to obtain fully recycled mold bag geopolymer concrete.

[0108] Example 9

[0109] 1. Preparation of composite alkali activator

[0110] Step A1: sugarcane bagasse, a solid waste from a sugar refinery, is calcined at 800° C. for 1 h and then ground in a ball mill for 40 min to obtain bagasse ash;

[0111] Step A2: Mix bagasse ash and 9M NaOH solution in a mass ratio of 1:4, and stir for 10 minutes to obtain a mixed solution;

[0112] Step A3: The mixed solution is sealed and stored, and allowed to stand for 24 hours to allow the bagasse ash to fully dissolve, thereby obtaining a composite alkali activator.

[0113] 2. Preparation of fully recycled geopolymer concrete

[0114] Step B1: Weigh the following components by mass: 280 parts of recycled coarse aggregate, 140 parts of recycled fine aggregate, 7 parts of composite alkali activator, 0.2 parts of polycarboxylic acid high-performance water reducer, and 30 parts of water. The geopolymer precursor is prepared by mixing 30 parts of recycled micro powder, 40 parts of fly ash, and 30 parts of slag;

[0115] Step B2: placing the geopolymer precursor and the recycled fine aggregate in a mixer and mixing them for 2 minutes, then adding the recycled coarse aggregate and stirring for 2 minutes to obtain a mixture;

[0116] Step B3: Take an appropriate amount of water to dissolve the high-performance water-reducing agent to obtain a high-performance water-reducing agent solution; then, add the composite alkali activator and the remaining water into the mixer, stir for 2 minutes, then add the high-performance water-reducing agent solution, stir for 2 minutes, and obtain a freshly mixed fully recycled geopolymer concrete.

[0117] 3. Preparation of fully recycled mold bag geopolymer concrete

[0118] Use a concrete pump to press the freshly mixed fully recycled geopolymer concrete into the mold bag, and control the pouring rate at 15m 3 / h, after being filled, use cable ties to tie it up, cover it with grass and sprinkle water for 3 days to obtain fully recycled mold bag geopolymer concrete.

[0119] Example 10

[0120] The preparation of the composite alkali activator, the raw material components, the preparation of the fully recycled geopolymer concrete and the mold bag concrete are the same as those in Example 4, except that the grass covering and watering curing time is 7 days.

[0121] Embodiment 11

[0122] The preparation of the composite alkali activator, the raw material components, the preparation of the fully recycled geopolymer concrete and the mold bag concrete are the same as those in Example 4, except that the grass covering and watering curing time is 14 days.

[0123] Example 1-11 Performance Test

[0124] According to GB / T 50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures" and GB / T50081-2019 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", the initial setting time, expansion and compressive strength of the fully recycled geopolymer concrete prepared in each embodiment were tested, and the test results are shown in Table 1.

[0125] Table 1 Performance test results of fully recycled geopolymer concrete

[0126]

[0127]

[0128] It can be seen from the data in the table that in Examples 1-3, in the binary precursor of geopolymer, the recycled micropowder and slag particles have a large specific surface area and strong water absorption. Therefore, in order to ensure fluidity, the amount of water or water reducer is increased compared with other groups, but the strength is slightly reduced. In Examples 4-6, it can be seen that due to the increase in the amount of composite alkali activator, the hydration process of geopolymer concrete is accelerated, and therefore the initial setting time is reduced. In addition, due to the increase in alkali activator, the consistency of the geopolymer slurry increases, resulting in a smaller expansion. Examples 7-9 show that increasing the calcination temperature accelerates the calcination efficiency, but also makes the bagasse ash more difficult to grind. Examples 4 and 10-11 show how the strength of geopolymer concrete changes with age.

[0129] The initial setting time of each embodiment is not less than 45 minutes, the expansion is greater than 500 mm, and the 3-day compressive strength is greater than 3 MPa. It has the characteristics of low hydration heat, high fluidity and rapid early strength development. The concrete can meet the engineering requirements of continuous construction and pumping of bagged concrete, and is used in canal waterways, slope protection and bank protection projects.

[0130] In summary, the fully recycled geopolymer concrete of the present invention uses recycled aggregates from construction waste as coarse and fine aggregates to replace natural aggregates, and replaces cement with a geopolymer cementitious material composed of a composite alkali activator prepared by mixing solid waste geopolymer precursors and bagasse ash instead of sodium silicate with NaOH solution, thereby achieving full regeneration and the synergy of multiple industrial solid wastes, providing a feasible path for the low-carbon and green application of concrete.

[0131] The above embodiments are only used to illustrate the present invention, rather than to limit the present invention. Those skilled in the relevant technical field may make various changes or modifications without departing from the spirit and scope of the present invention. Therefore, all equivalent technical solutions should also belong to the scope of the present invention and should be defined by the claims.

Claims

1. A fully recycled geopolymer concrete, characterized in that: The composition comprises the following components in parts by weight: Wherein, the geopolymer precursor includes at least one of recycled micro powder, fly ash and slag.

2. The fully recycled geopolymer concrete according to claim 1, characterized in that: The preparation method of the composite base activator comprises the following steps: (1) calcining bagasse at 600-800° C. for 1-2 hours and grinding the bagasse to obtain bagasse ash; (2) The bagasse ash obtained in step (1) is mixed with 7-9M NaOH solution in a mass ratio of 1:4 to obtain a mixed solution, and the mixed solution is allowed to stand for 12-36 hours to obtain a composite alkali activator.

3. The fully recycled geopolymer concrete according to claim 1, characterized in that: The components of the geopolymer precursor are, by weight, 30-50 parts of recycled micropowder, 0-40 parts of fly ash, and 30-70 parts of slag.

4. The fully recycled geopolymer concrete according to claim 1, characterized in that: The recycled coarse aggregate is obtained from the demolished concrete of abandoned buildings, abandoned dams or abandoned rivers after crushing, particle shaping and screening, and its particle grading is a continuous aggregate of 5-16mm, and the coarse aggregate grade is Class II and above; The recycled fine aggregate is obtained from mortar blocks of abandoned buildings, abandoned dams or abandoned rivers after crushing, particle shaping and screening, and its particle grading is a continuous aggregate of 0.15-4.75 mm, and the fine aggregate grade is Class II and above; The regenerated micro powder is obtained by grinding, magnetic separation and secondary grinding of waste sintered clay bricks, and its technical index is level II or above.

5. The fully recycled geopolymer concrete according to claim 1, characterized in that: The water reducer is at least one of a naphthalene-based water reducer, a polycarboxylic acid water reducer and a sodium lignin sulfonate water reducer.

6. A method for preparing the fully recycled geopolymer concrete as claimed in claim 1, characterized in that: The following steps are included: (1) Weighing each component according to the ratio, mixing the geopolymer precursor and the recycled fine aggregate evenly, and then adding the recycled coarse aggregate and mixing evenly to obtain a mixture; (2) mixing the water reducer with part of the water to obtain a water reducer solution; (3) Add the composite alkali activator and the remaining amount of water to the mixture obtained in step (1), mix them evenly, then add the water reducer solution obtained in step (2), mix them evenly, and obtain fully recycled geopolymer concrete.

7. A fully recycled mold bag geopolymer concrete, characterized in that: The method for preparing the fully recycled geopolymer concrete in mold bags comprises pressing the fully recycled geopolymer concrete prepared by the preparation method described in any one of claims 1 to 5 or claim 6 into a mold bag at a pouring rate of 5 to 20 m / s. 3 / h, and curing for 3-14 days to obtain fully recycled mold bag geopolymer concrete.

8. The fully recycled mold bag geopolymer concrete described in claim 7 is used in canal waterways, slope protection and bank protection projects.

Citation Information

Patent Citations

  • Hydraulic bag concrete using industrial solid wastes

    CN101456705A